Uniform and couniform dimensions of inverse polynomial modules over skew Ore polynomials - Higuera, Sebastian; Reyes, Armando (International electronic journal of algebra, 2025)
In this paper, we study the uniform and couniform dimensions of inverse polynomial modules over skew Ore polynomials.